Safety and immunogenicity of a prototype anti-Chlamydia pecorum recombinant protein vaccine in lambs and pregnant ewes. Issue 27 (14th June 2017) - Desclozeaux, Marion; Jelocnik, Martina; Whitting, Katrina; Saifzadeh, Siamak; Bommana, Sankhya; Potter, Andrew; Gerdts, Volker; Timms, Peter; Polkinghorne, Adam
Highlights: An anti C. pecorum SC-vaccine is safe to use in pregnant sheep and lambs. The SC-vaccine triggers production of C. pecorum -specific serum IgG and secretory IgA. The SC-vaccine also promotes production of cytokine IFN-γ. A Boost vaccination further stimulates both humoral and cell-mediated immune responses in lambs. Abstract: Arthritis and kerato-conjunctivitis caused by Chlamydia pecorum in lambs are difficult to diagnose and treat. We tested the ability of a prototype C. pecorum vaccine (SC-vaccine), comprised of C. pecorum major outer membrane protein (MOMP-G) and polymorphic membrane protein G (PmpG), to trigger a Chlamydia -specific humoral and cell-mediated immune response in lambs and pregnant ewes. Vaccinations with the SC-vaccine (one and two injections) were very well tolerated by all ewes and lambs. Although the overall immune responses of ewes to SC-vaccination was poor, their lambs showed stronger antigen-specific immune response than lambs from control vaccine ewes. SC-vaccination in lambs triggered production of systemic anti-MOMP-G and anti-PmpG IgG antibodies and secretory IgA in the ocular mucosa. Double vaccination caused statistically significant increases in the height and duration of the humoral response. Antigen-specific IFN-γ was produced in the peripheral blood mononuclear cells of vaccinated lambs.